Modulation of pro- and anti-inflammatory cytokines in active and latent tuberculosis by coexistent Strongyloides stercoralis infection. Issue 6 (December 2015) - George, Parakkal Jovvian; Pavan Kumar, Nathella; Jaganathan, Jeeva; Dolla, Chandrakumar; Kumaran, Paul; Nair, Dina; Banurekha, Vaithilingam V.; Shen, Kui; Nutman, Thomas B.; Babu, Subash
Summary: Helminth infections are known to induce modulation of both innate and adaptive immune responses in active and latent tuberculosis (TB). However, the role of helminth infections in modulating systemic cytokine responses in active and latent tuberculosis (LTB) is not known. To define the systemic cytokine levels in helminth-TB coinfection, we measured the circulating plasma levels of Type 1, Type 2, Type 17, other pro-inflammatory and regulatory cytokines in individuals with active TB (ATB) with or without coexistent Strongyloides stercoralis (Ss) infection by multiplex ELISA. Similarly, we also measured the same cytokine levels in individuals with LTB with or without concomitant Ss infection in a cross-sectional study. Our data reveal that individuals with ATB or LTB and coexistent Ss infection have significantly lower levels of Type 1 (IFNγ, TNFα and IL-2) and Type 17 (IL-17A and IL-17F) cytokines compared to those without Ss infection. In contrast, those with ATB and LTB with Ss infection have significantly higher levels of the regulatory cytokines (IL-10 and TGFβ), and those with LTB and Ss infection also have significantly higher levels of Type 2 cytokines (IL-4, IL-5 and IL-13) as well. Finally, those with LTB (but not ATB) exhibit significantly lower levels of other pro-inflammatory cytokines (IFNα, IFNβ, IL-6, IL-12 and GM-CSF). Our data therefore reveal a profound effect of Ss infection on the systemic cytokine responses in ATB and LTB and indicate that coincident helminth infections might influence pathogenesis of TB infection and disease.